Code of Conduct. - Michaels, J. C. (Philosophy Now)
The article centers on Kye, a programmer grappling with corporate immorality and personal ethical responsibility within a technology company led by a confrontational Chief Technology Officer, Lex. It explores themes of trust, individual agency, and the moral dilemmas faced by employees asked to implement invasive data-harvesting practices justified by opaque user agreements. Drawing on philosophical references such as Plato’s story of Gyges’ ring, the narrative questions whether people can act ethically when unobserved and highlights the tension between corporate demands and personal values. Ultimately, Kye resigns in protest, advocating for transparency through open-source solutions as a means to address systemic ethical failures in the tech industry.